23 Frailty, Older Age-Associated Conditions, and Multimorbidity Amongst People Experiencing Homelessness in A Hostel in London. (16th March 2021) - Rogans-Watson, R; Shulman, C; Lewer, D; Armstrong, M; Hudson, B
Abstract: Introduction: People experiencing homelessness (PEH) face poor health outcomes and extreme health inequity, and evidence suggests earlier onset of older age-associated conditions and signs of premature ageing. This is the first UK study to assess frailty in this population. The objective was to assess frailty, age-associated conditions, and multimorbidity in PEH residing in hostel accommodation, drawing comparisons with population data. Methods: Participants were drawn from a hostel in London for PEH aged over 30. Age-associated conditions were identified using validated tools and a questionnaire modelled on comprehensive geriatric assessments. Participants' keyworkers completed questionnaires to provide collateral information. Frailty was defined according to five criteria in Fried's phenotype model: participants with three or more criteria are classified as frail, one or two criteria as vulnerable, and no criteria as not frail. Multimorbidity was defined as the presence of two or more long-term conditions in one person. Comparisons were made with population data from The English Longitudinal Study of Ageing and Health Survey for England. Results: Thirty-three people participated (83% of eligible residents), with a mean age of 55.7 years (range 38–74). Frailty was identified in 18/33 participants (55%), with 13/33 (39%) classified as vulnerable, and 2/33 (6%) as not frail. Participants met an average of 2.6/5 frailty phenotype criteria, comparable to 90-year-olds in the general population. The most common age-associated conditions identified were: falls (in 61%), visual impairment (61%), low grip strength (61%), mobility impairment (52%), and cognitive impairment (45%). Multimorbidity was present in all thirty-three participants. Conclusions: A wide range of unmet health needs was identified. The high prevalence of frailty and age-associated conditions support evidence of premature ageing, indicating a need to include holistic older-age assessments in PEH at a younger age. Involvement of health professionals with experience of working with older people could contribute to improving health outcomes for homeless patients.